Efficacy and Safety of Preoperative vs. Intraoperative Computed Tomography-Guided Lung Tumor Localization: A Randomized Controlled Trial - Fang, Hsin-Yueh; Chen, Kuei-An; Wen, Yu-Wen; Wen, Chih-Tsung; Pan, Kuang-Tse; Chiu, Chien-Hung; Hsieh, Ming-Ju; Chao, Yin-Kai (Frontiers in Surgery, 2022)
Background Thoracoscopic removal of small pulmonary nodules is traditionally accomplished through a two-step approach – with lesion localization in a CT suite as the first step followed by lesion removal in an operating room as the second step. While the advent of hybrid operating rooms (HORs) has fostered our ability to offer a more patient-tailored approach that allows simultaneous localization and removal of small pulmonary nodules within a single-step, randomized controlled trials (RCTs) that compared the two techniques (two- versus single-step) are still lacking. Methods This is a RCT conducted in an academic hospital in Taiwan between October 2018 and December 2019. To compare the outcomes of traditional two-step preoperative CT-guided small pulmonary nodule localization followed by lesion removal versus single-step intraoperative CT-guided lesion localization with simultaneous removal performed by a dedicated team of thoracic surgeons.The analysis was conducted in an intention-to-treat fashion. The primary study endpoint was the time required for lesion localization. Secondary endpoints included radiation doses, other procedural time indices, and complication rates. Results A total of 24 and 25 patients who received the single- and two-step approach, respectively, were included in the final analysis.The time required for lesion localization was significantly shorter for patients who underwent the single-step procedure (median: 13 min) compared with the two step-procedure (median: 32 min, p<0.001). Similarly, the radiation dose was significantly lower for the former than the latter (median: 5.64 msv versus 10.65 msv, respectively, p=0.001). Conclusions The single-step procedure performed in a hybrid operating room resulted in a simultaneous reduction of both localization procedural time and radiation exposure. Trial Registration: ClinicalTrials.gov identifier: NCT03395964